From genomics to targeted treatment in haematological malignancies: a focus on acute myeloid leukaemia - Jakobsen, N; Vyas, P (Royal College of Physicians, 2018)
The haematological malignancies are a heterogeneous group of neoplastic disorders, which lead to almost 10,000 deaths annually in the UK. Over the past 2 decades, there has been significant progress in our understanding of the pathological mechanisms underlying these cancers, accompanied by improvements in outcomes for some patients. In particular, advances in next-generation sequencing now make it possible to define the genetic lesions present in each patient, which has led to improved disease classification, risk stratification and identification of new therapeutic targets. Here we discuss recent advances in the genomic classification and targeted treatment of haematological malignancies, focusing on acute myeloid leukaemia. Multiple novel drug classes are now on the horizon, including agents that target overactive signalling pathways, differentiation therapies and immunotherapies. By combining molecular diagnostics with targeted therapy, the management of these diseases is set to change radically over the coming years.